Airn Regulates Igf2bp2 Translation in Cardiomyocytes - Hosen, Mohammed Rabiul (Circ Res, 2018)
RATIONALE: Increasing evidence indicates the presence of long noncoding RNAs (lncRNAs) in various cell types. Airn is an imprinting gene transcribed from the paternal chromosome. It is in antisense orientation to the imprinted, but maternally-derived, Igf2r gene, on which Airn exerts its regulation in cis. Although Airn is highly expressed in the heart, functions aside from imprinting remain unknown. OBJECTIVE: Here, we studied the functions of Airn in the heart, especially cardiomyocytes. METHODS AND RESULTS: Silencing of Airn via siRNAs augmented cell death, vulnerability to cellular stress, and reduced cell migration. To find the cause of such phenotypes, the potential binding partners of Airn were identified via RNA pull-down followed by mass spectrometry, which indicated Igf2bp2 and Rpa1 as potential binding partners. Further experiments showed that Airn binds to Igf2bp2 to control the translation of a number of genes. Moreover, silencing of Airn caused less binding of Igf2bp2 to other mRNAs and reduced translation of Igf2bp2 protein. CONCLUSIONS: Our study uncovers a new function of Airn and demonstrates that Airn is important for the physiology of cardiomyocytes.